Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
The equation of a line parallel to \( y = 4x - 1 \) through \( (1, 3) \) is \( y = 4x - 1 \).
To find the equation of a line parallel to a given line, we need to understand that parallel lines have the same gradient (or slope). The given line \( y = 4x - 1 \) has a gradient of 4. This is because the equation is in the form \( y = mx + c \), where \( m \) represents the gradient. Therefore, any line parallel to this one will also have a gradient of 4.
Next, we need to find the specific equation of the line that passes through the point \( (1, 3) \). We use the point-gradient form of a line equation, which is \( y - y_1 = m(x - x_1) \), where \( (x_1, y_1) \) is a point on the line and \( m \) is the gradient. Substituting \( m = 4 \), \( x_1 = 1 \), and \( y_1 = 3 \) into the formula, we get:
\[ y - 3 = 4(x - 1) \]
Expanding and simplifying this equation:
\[ y - 3 = 4x - 4 \]
\[ y = 4x - 1 \]
So, the equation of the line parallel to \( y = 4x - 1 \) that passes through the point \( (1, 3) \) is indeed \( y = 4x - 1 \). This shows that the new line has the same gradient and passes through the given point, confirming it is parallel to the original line.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.